Question Answering System at the Kingdom of Sumedang Larang with Naïve Bayes Method - Richo Fedhia Saldhi; Z.K.A. Baizal; Ramanti Dharayani (Journal of Computer System and Informatics (JoSYC), 2022)
The Sumedang Larang Kingdom is one of the kingdoms in Indonesia which was founded by Prabu Tajimalela in 721 AD. The Sumedang Larang Kingdom is known as the national history of Indonesia. Still, most of the current generation does not know the history of the Sumedang Larang Kingdom, especially the younger generation. Therefore, we developed a question-and-answer system to seek information about the Sumedang Larang Kingdom. With the development of information technology, research on question answering systems is applied to research on Biomedical Questions to produce correct answers. Our system will help literacy about the Sumedang Larang Kingdom for the younger generation, especially students, and increase Indonesian cultural assets. The QA system aims to generate and provide precise short answers to user questions by automatically using information extraction and natural language processing methods. To collect and create questions, we use the concept of ontology. In addition, we use the Natural Language Naïve Bayes method to answer user questions. We built a QA system that can help students find information about the history of the Sumedang Larang Kingdom. Based on the accuracy of the results of testing the method we propose. In our evaluation, we involve the Decision Tree method as the base model. We note that the accuracy of the Naïve Bayes method is higher than that of the Decision Tree. The accuracy result of Naïve Bayes at the ratio of 8:2 and 7:3 is 67%, while the Decision Tree is only 56%.